# Find an equation of the tangent line to the curve y=sin(3x) +cos(2x)at the point (pi/6, y(pi/6)). Tangent line:

*print*Print*list*Cite

You need to remember what equation of tangent line to a curve at a point is:

`y - y_0 = f'(x_0)(x - x_0)`

You need to identify what are the `x_0` and `y_0` coordinates of the point of tangency, hence, the problem provides that `x_0=pi/6` and `y_0=sin 3pi/6 + cos 2pi/6 = 1 + 1/2 = 3/2` .

You need to differentiate the function with respect to x such that:

`f'(x) = (sin 3x + cos 2x)'`

You need to use chain rule to differentiate the function such that:

`f'(x) = 3cos 3x - 2 sin 2x`

You need to substitute `pi/6` for x in `f'(x)` such that:

`f'(pi/6) = 3 cos 3(pi/6) - 2 sin 2(pi/6)`

`f'(pi/6) = 3 cos (pi/2) - 2 sin (pi/3)`

Since `sin (pi/3) = sqrt3/2` and `cos(pi/2) =0` yields:

`f'(pi/6) = - 2 sqrt3/2`

`f'(pi/6) = -sqrt3`

You need to substitute `pi/6` for `x_0` , `3/2` for `y_0` and `-sqrt3` for `f'(x_0)` in equation of tangent line such that:

`y -3/2 = -sqrt3(x - pi/6)`

You need to use the slope intercept form of equation of tangent line, hence, you need to isolate y to the left side such that:

`y = -sqrt3*x - pi*sqrt3/6 + 3/2`

**Hence, evaluating the equation of tangent line to the graph `y=sin(3x) +cos(2x)` , at (pi/6,3/2) yields`y = -sqrt3*x - pi*sqrt3/6 + 3/2.` **